Simulations of the thermo-acoustic lens effect during focused ultrasound surgery. - Hallaj, I; Cleveland, R; Hynynen, K (2001)
Laboratory measurements of soft tissue properties show a dependence of background propagation properties on temperature. For typical focused ultrasound surgery (FUS) applications, only the slow variations in tissue background parameters need to be accounted for when computing the outcome of a FUS sonication. The cumulative effect of slowly varying sound speed has been referred to in the literature as a thermal lens, or a thermo-acoustic lens because of its beam-distorting properties. An algorithm to solve the coupled acoustic-thermal problem is described, and numerical results are presented to illustrate the effects of dynamic sound-speed profiles in layered tissues undergoing FUS. The results of simulations in liver with and without a fat layer indicate that the thermal-acoustic interaction results in more complex dynamics in FUS than a simple model will predict. Both the size and the position of the lesions predicted from the simulations are affected by the thermo-acoustic lens effect. However, the overall effect from short sonications at high power from sharply focused single element sources (F-no. from 0.8 to 1.3) around 1 MHz similar to those used in clinical setups is found to be small.